Performance Comparision of Single Slope Solar Still Loaded With Various Nano-Fluids - Kumar, Vijay (My University, 2019)
In the present work, a thermal model of single slope basin type solar still (passive type) was developed (using Runga-kutta ODE) and validated with the experimental results carried out for the location Patiala, which is in a good agreement to each other, then the model was further modified by integrating different Nanofluids at different volume fractions 0.02, 0.05, 0.08, 0.12 and 0.2. The analysis for modified still has been carried out for optimised water depth of 0.02 m with different nanofluids. Yield obtained for nanofluid Al2O3 was 14.22% higher than simple solar still without nanofluid, followed by CuO 10.82%, Ag 8.11%, Fe2O3 7.63%, and SiC 7.61%. The effects of various parameters like water depth and volume fraction of the nanofluid were compared. It has been found that the optimum volume concentrations for maximum distillate output of different water based-nanofluid was 0.2 for Al2O3, 0.2 for CuO, 0.02 for Ag, 0.05 for Fe2O3, and 0.2 for SiC, and with the increase in water levels the performance of still decreases because of the sensible heat storage in the fluid, and by increasing the volume fraction of nanofluid, heat transfer coefficients increases but after certain values efficiency curve becomes linear with no change.
M.Tech Thesis
Keywords: Solar still; Single slope; Thermal model; Nano-fluid; Solar desalination; Single glass solar still